A General Method to Diverse Cinnolines and Cinnolinium Salts. Issue 20 (28th March 2013) - Zhao, Dongbing; Wu, Qian; Huang, Xiaolei; Song, Feijie; Lv, Taiyong; You, Jingsong
<x xml:space="preserve">Abstract</x> Rhodium catalysis: A highly efficient and general method has been established to prepare cinnolines, cinnolinium salts, and polycyclic cinnolinium salts through the rhodium(III)‐catalyzed oxidative CH activation/cyclization of azo compounds with alkynes (see scheme). Key features of this methodology include the unprecedented capacity to create both cinnoline and cinnolinium frameworks.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>